Conceptual model for secure smart home energy management - saleh, abdulaziz (Journal of Computing Technologies and Creative Content, 2019)
Smart Home Energy Management (SHEM) systems is the main Internet of Things (IoT) application related to home energy control and consumption management. SHEM systems include subsystems which are used for monitoring, logging, control, management and alarms . Such subsystems might be potentially exposed to different kinds of security threats. Defining a security model for SHEM systems is a very complicated task due to its heterogeneous and dynamic structure. It contains millions or billions of objects that communicate with each other and with human beings. Furthermore, defining a security model for SHEM systems is not an easy task because of it is deployed in an open environment which makes the attackers’ job easier.This study proposes a system design and architecture for secure SHEM systems based on game theory.  It focuses on analyzing  SHEM systems security vulnerabilities then selecting most effect defense methods based on game theory principles.  An objective of this study was to propose conceptual model for secure smart home energy management.  Keywords— Smart Home, Energy Management, games theory, SDN